Implementasi RPOA-IUU di Kawasan Asia Tenggara - Mauly Dini Budiyanti; Arfin Sudirman (Jurnal Hubungan Internasional, 2019)
Southeast Asia is one of the areas vulnerable to IUU Fishing. This problemhas transnational characteristics starting from location, perpetratorand flag of the ship. The perpetrators of IUU Fishing mostly come fromneighboring countries. Therefore, handling this problem requires ajoint role and commitment. One of the regional measures in dealingthis problem is through Regional Plan of Action to Promote ResponsibleFishing Practices including Combating IUU Fishing (RPOA-IUU) whichcontains various recommendations for actions to promote responsibleand sustainable fishing. This paper will discuss the capabilities andwillingness of RPOA-IUU implementation by its five member countries,Indonesia, Malaysia, Philippines, Thailand and Vietnam, as well as theimplementation gap that arises when the actual implementation of eachcountry is not in accordance with what has been agreed. This paper usesdescriptive qualitative methods in explaining the implementation of theRPOA IUU by each country and also uses the regime implementationtheory to analyze the implementation gap in the RPOA-IUU.